Xth International Symposium Biomechanics and Medicine in Swimming, Porto, Portugal, June 21 to 24, 2006 (2006)
Website of the Xth International Symposium Biomechanics and Medicine in Swimming, Porto, Portugal, June 21 to 24, 2006.